Herbacetin, A Constituent of Ephedrae herba, Suppresses the HGF-Induced Motility of Human Breast Cancer MDA-MB-231 Cells by Inhibiting c-Met and Akt Phosphorylation - Hyuga, Sumiko; Hyuga, Masashi; Yoshimura, Morio; Amakura, Yoshiaki; Goda, Yukihiro; Hanawa, Toshihiko (Planta Medica, 2013)
Ephedrae herba suppresses hepatocyte growth factor-induced cancer cell motility by inhibiting tyrosine phosphorylation of the hepatocyte growth factor receptor, c-Met, and the PI3K/Akt pathway. Moreover, Ephedrae herba directly inhibits the tyrosine-kinase activity of c-Met. Ephedrine-type alkaloids, which are the active component of Ephedrae herba, do not affect hepatocyte growth factor-c-Met-Akt signalling, prompting us to study other active molecules in the herb. We recently discovered herbacetin glycosides and found that their aglycon, herbacetin, inhibits hepatocyte growth factor-c-Met-Akt signalling. This study revealed a novel biological activity of herbacetin. Herbacetin suppressed hepatocyte growth factor-induced motility in human breast cancer MDA-MB-231 cells by inhibiting c-Met and Akt phosphorylation and directly inhibiting c-Met tyrosine kinase activity. The effects of herbacetin were compared to those of kaempferol, apigenin, and isoscutellarein, all of which have similar structures. Herbacetin inhibition of hepatocyte growth factor-induced motility was the strongest of those for the tested flavonols, and only herbacetin inhibited the hepatocyte growth factor-induced phosphorylation of c-Met. These data suggest that herbacetin is a novel Met inhibitor with a potential utility in cancer therapeutics.
Keywords: herbacetin; c-Met; hepatocyte growth factor; cancer cell motility; Ephedrae herba; Ephedraceae